Unusual substituent effects in the Tr···Te triel bond. Issue 6 (30th October 2020) - Wang, Ruijing; Luo, Canlin; Li, Qingzhong; Scheiner, Steve
Abstract: The triel bond between the π‐hole on the triel atom of TrR3 (Tr = B, Al, Ga; R = H, F, Cl, Br) and a lone pair on the Te atom of H2 Te is examined using ab initio methods. For Tr = B, the triel bond is weakened as the R substituent becomes more electronegative, while the opposite pattern is noted for Al and Ga. The weakest triel bond of all occurs in H2 Te‐BF3 (2.9 kcal/mol) but is much stronger for all the other complexes (>11 kcal/mol). The placement of electron‐releasing OH, NH2, and CH3 R′ substituents on the R′2 Te base strengthens the triel bond, whereas the opposite occurs for the electron‐withdrawing CN. Despite its high electronegativity, the F substituent causes a strengthening of the interaction, which is due in large part to the formation of secondary chalcogen bonds that involve the σ‐holes on Te in F2 Te. However, the F atom on TrF3 is unable to act as an electron donor in these chalcogen bonds, leading to weakened F2 Te··TrF3 interactions. Abstract : The Te atom is first utilized to bind with the π‐hole of TrR3 (Tr = B, Al, Ga; R = H, F, Cl, Br). The effect of halogen substitution in TrR3 on the triel bond is related to the nature of the triel atom. The electron‐releasing OH, NH2, and CH3 substituents on the R′2 Te base strengthen the triel bond, whereas the opposite occurs for the electron‐withdrawing CN. However, the F substituent causes a strengthening of the interaction.